The Role of Halal Supply Chain Management for Slaughter Chicken Business Actors (Case Study of Slaughter Chicken Business in Gunung Manaon Village 1) - Halimah Safitry Al-Fauziah; Muhammad Rafli; Siti Aisyah (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2022)
Chicken meat is one of the products that are in great demand and consumed by the people of Indonesia. Indonesian people generally consume more chicken meat with an average of 7 kg of meat per year compared to consuming beef. North Sumatra is no exception, especially in the village of Gunung Manaon 1. So the purpose of this study is to find out whether the beef chicken business in the village of Gunung Manaon 1 is in accordance with Islamic law, both in the production process, distribution and when it arrives at hand. consumers and what is the role of halal supply chain management in this beef chicken business. The research method used is a qualitative method using descriptive by conducting field observations and direct interviews with business owners, employees and consumers. And from the results of this study, we found that the Chicken Slaughter Business in Gunung Manaon 1 Village was in accordance with existing halal laws. In addition, supply chain management activities in the Chicken Slaughterhouse have also met halal standards according to interview and observation data. Then for the provision of animal feed and the like, it is also necessary to ensure the validity of feed and beverage ingredients, vaccines and vitamins that do not directly affect chicken meat, but this is done to avoid suspicious things....